2012
DOI: 10.1007/s10096-012-1623-9
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and evolution of antibiotic resistance of Haemophilus influenzae in children 5 years of age or less in France, 2001–2008: a retrospective database analysis

Abstract: Trends in the evolution of antimicrobial resistance and mechanisms of resistance of Haemophilus influenzae to β-lactam antibiotics in France were assessed through a retrospective database review. The antimicrobial resistance of 2,206 H. influenzae strains from children aged ≤5 years was studied between 2001 and 2008. Strains were isolated from blood or cerebrospinal fluid (n = 170), bronchial secretions (n = 188), middle ear fluid, and nasopharynx or conjunctiva (n = 1,848). A proportion of 95.1 % (n = 2,097) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 29 publications
3
33
0
2
Order By: Relevance
“…4,5,7 In a number of European countries and the US, BLNAR isolates are less common and most strains with PBP3 substitutions are group I or II. 6,22,23,26,27 In contrast, BLNAR isolates in Japan tend to be group III strains that mainly have PBP3 substitutions. 5,28,29 In fact, 88.7% of gBLNAR strains were classified as group III in this study.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…4,5,7 In a number of European countries and the US, BLNAR isolates are less common and most strains with PBP3 substitutions are group I or II. 6,22,23,26,27 In contrast, BLNAR isolates in Japan tend to be group III strains that mainly have PBP3 substitutions. 5,28,29 In fact, 88.7% of gBLNAR strains were classified as group III in this study.…”
Section: Discussionmentioning
confidence: 87%
“…Reduced susceptibility to ampicillin was found in 68.8% of the isolates (26.7% were low-BLNAR, 33.8% were BLNAR, 4.5% were BLPAR and 3.8% were BLPACR), which is similar to the findings of a recent Japanese study performed in pediatric patients by Hoshino et al 8 In Japan, the prevalence of β-lactamase-producing isolates is lower and that of BLNAR isolates is higher compared with other countries because the percentage of β-lactamase-positive/BLNAR (including low-BLNAR) isolates in the US, France and Korea was reported to be 28.3/0.7, 27.3/16.9 and 52.4/6.1 %, respectively. [22][23][24] This study showed that amino acid substitutions of PBP3 were the most prevalent mechanism of ampicillin resistance for H. influenzae. According to the PCR-based genotyping of H. influenzae demonstrated that all of the BLNAR strains had amino acid substitutions related to ampicillin resistance (gBLNAR).…”
Section: Discussionmentioning
confidence: 95%
“…An obvious limitation of this method is the inability to detect b-lactamase-negative ampicillin-resistant (BLNAR) isolates encoding altered penicillin-binding proteins through mutation in the ftsI gene conferring resistance (Ubukata et al, 2001). A review of the literature failed to find reports of BLNAR isolates among Hif isolates, and the BLNAR phenotype is rare in North America in general, but evidence does suggest that, in areas of Europe and Asia, there is increasing prevalence of BLNAR isolates among non-typable and serotype b isolates, suggesting that future studies on antimicrobial susceptibility patterns should include methods to capture these strains as well (Hasegawa et al, 2006;Dabernat & Delmas, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Isolates with high-level resistance (high-rPBP3) are a major clinical problem in Japan and South Korea [15-17] whereas low-level resistant (low-rPBP3) isolates so far predominate in the rest of the world [4,11,12,14,18-21]. Group II isolates with a characteristic substitution pattern, PBP3 type A (D350N, M377I, A502V, N526K, V547I and N569S) [11], and compatible patterns (identical to PBP3 type A as far as comparison is possible) are particularly common [3,4,9,11,12,16,18,20],[22-25].…”
Section: Introductionmentioning
confidence: 99%